Travel Intention and Travel Behaviour in the Post-Pandemic Era: Evidence from Vietnam - Ha My, Duong Tien; Le Thanh, Tung (Organizations and Markets in Emerging Economies, 2023)
Tourism is on the pathway of returning and contributes to the economic development of many countries. Understanding the decision-making process of tourism customers in the post-pandemic context is crucial for a strong recovery of the tourism sector. The paper aims to identify the determinants of travel intention and the link between travel intention and travel behaviour in the post-COVID-19 pandemic period. A total number of 431 questionnaires regarding the individual behaviour of Vietnamese travellers were collected. The empirical results reveal that electronic word of mouth, crisis management, and destination image in COVID have positive relationships with travel intention. Besides, travel intention is positively linked with the customers’ travel behaviour during the post-pandemic era. By contrast, the results do not support the conclusion regarding the relationship between risk communication, the healthcare system, non-pharmaceutical interventions and the travel intention of customers. Finally, the practical implications are included for enhancing a faster recovery process of the tourism sector.
Keywords: travel intention; travel behaviour; post-pandemic; tourism development; tourism recovery; global tourism